Screening medical patients for depression: lessons from a national program in cancer clinics - Walker, J; Wanat, M; Fielding, J; Martin, P; Petit, A; Burke, K; Sharpe, M (Elsevier, 2017)
Background: Screening has been recommended to improve the identification of depression in medical patients. There is therefore a need for useful practical information on how to successfully implement large scale depression screening in medical clinics. Objective: To describe the practical lessons learned from our experience of implementing a large scale depression screening program in cancer clinics throughout Scotland, UK. Method: Reflective review based on the experience of the screening team and records of the iterative development of the program. Findings: Systematic screening for depression in patients with medical illnesses can be delivered in clinics as long as the program is well designed. Design issues include ensuring the engagement of staff and patients, implementing efficient two stage screening processes and effectively managing workflow and quality assurance. Discussion: Screening has the potential to offer a solution to the well documented problem of missed depression and other psychiatric diagnoses and to thereby improve patient care if closely linked to treatment provision.